Laparoscopic pancreas-preserving subtotal duodenectomy for gastrointestinal stromal tumor. Issue 3 (June 2013) - Corcione, Francesco; Pirozzi, Felice; Sciuto, Antonio; Galante, Francesco; Bracale, Umberto; Andreoli, Federica
Abstract Gastrointestinal stromal tumors (GISTs) of the duodenum are rare neoplasms. The optimal surgical procedure is debated and several options ranging from limited resections to pancreaticoduodenectomy have been reported. The laparoscopic approach has been validated for gastric GISTs, but it does not yet represent a standard technique for tumors of the duodenum. We report the case of a localized duodenal GIST that was successfully treated by totally laparoscopic pancreas-preserving subtotal duodenectomy. This procedure may represent a feasible and effective treatment option for localized GISTs of the duodenum. Large series with long-term follow-up are needed.